Shexiang Baoxin Pill (MUSKARDIA) reduces major adverse cardiovascular events in women with stable coronary artery disease: A subgroup analysis of a phase IV randomized clinical trial - Shi, Haiming; Zhou, Jingmin; Ma, Changsheng; Ji, Fusui; Wu, Yang; Zhao, Yulan; Qian, Jun; Wang, Xiaolong (Frontiers in Cardiovascular Medicine, 2022)
Background: A previous phase IV trial revealed sex as a potential effect modifier of MUSKARDIA efficacy in stable coronary artery disease (CAD). Objective: To assess the clinical effect of MUSKARDIA as a supplemental treatment to optimal medical therapy (OMT) in stable CAD cases. Methods: This study was a subgroup analysis of a multicenter, randomized, double-blinded, placebo-controlled phase IV clinical study. Eligible individuals underwent randomization to the oral MUSKARDIA and placebo groups and were treated for 24 months. All participants received OMT according to existing guidelines. The primary composite outcome was the major adverse cardiovascular event (MACE), included cardiovascular death, non-fatal myocardial infarction (MI), or non-fatal stroke. The secondary composite outcome encompassed all-cause mortality, non-fatal MI, non-fatal stroke, hospitalization for unstable angina and/or heart failure, and undergoing coronary procedure/surgery during treatment. Safety signals, especially cardiovascular adverse events (AEs), were analyzed. Results: The female subgroup included 776 participants (384 and 392 in the MUSKARDIA and placebo groups, respectively). The occurrence of the primary composite outcome was lower in the MUSKARDIA group compared with placebo-treated individuals (HR=0.27, 95%CI: 0.09-0.83; P=0.02), but the secondary composite outcome showed no significant difference (HR=0.77, 95%CI: 0.47-1.25; P=0.29). The MUSKARDIA group had reduced incidence of cardiovascular AEs compared with placebo-treated cases (2.9% vs. 5.6%). Conclusion: As a supplemental treatment to OMT, 24-month administration of MUSKARDIA is effective and safe in female stable CAD cases. Trial registration: ClinicalTrials.gov, NCT01897805.